A framework for antecedents of social entrepreneurial intention: Empirical evidence and research agenda - Bergner, Sabine; Palmer, Carolin; Devaney, Megan; Kruse, Philipp (Frontiers in Psychology, 2022)
Social entrepreneurship (SE) increasingly contributes to diversity in entrepreneurship. The different approaches to SE suggest a variety of antecedents which drive individuals’ intention to become social entrepreneurs. While this variety of antecedents is insightful, it also creates a need for systemisation and prioritisation. We address this need by introducing an integrative, multi-level framework for person-based antecedents of SE-intention. Based on this multi-level framework the antecedents are grouped on three theoretical levels which refer to an individual’s 1) personality, 2) cognition, and 3) entrepreneurial exposition. When testing our framework with 499 South African university students we find support for the multi-level framework and its notion that antecedents from the multiple levels complement each other. Therefore, this study provides a structure for person-based antecedents of SE-intention and additionally points to future research which may extend the proposed framework.